First report of vancomycin resistant Enterococcus faecalis and Enterococcus faecium isolated from water buffalo clotted cream in Turkey: First report of VR E. faecalis and E. faecium from buffalo clotted cream - Seker, E; Dogan, YN (Journal of the Hellenic Veterinary Medical Society, 2023)
This study aimed to isolate the Enterococcus species from homemade water buffalo clotted cream sold in Afyonkarahisar, investigate the vancomycin resistance genes in isolated strains by PCR and determine the antibiotic resistance of strains to some antibiotics commonly used in Turkey. A total of 107 buffalo clotted cream samples sold in public bazaars of Afyonkarahisar were collected. Following the phenotypic identification using a commercial identification kit, PCR was applied to strains using by species specific primers. Forty Enterococcus strains were obtained from 107 samples by PCR. Of 40 strains, 31 (77.5%) and 9 (22.5%) were identified to be E. faecalis and E. faecium, respectively. One vanA (2.5%) and 14 vanB (35%) genes were determined in tested 40 strains. While of strains having the vanB gen, 10 and four were found to be E. faecalis and E. faecium, respectively, one E. faecium strain also harboured the vanA gen. Thus, while the vanB gen positivity was found to be 32.3% in 31 E. faecalis strains and 44.4% in 9 E. faecium strains, the vanA gen positivity was determined to be 11.1% in 9 E. faecium strains. It was not found the vanC1 and vanC2/C3 genes in none of the strains. While all of strains were phenotypically resistant to streptomycin and fusidic acid, high resistance rates were also determined in the strains to kanamycin (87.5%), cephalothin (80%), erythromycin (80%), gentamicin (77.5%), tetracycline (75%) and vancomycin (60%). Resistance to all tested antibiotics except teicoplanin was determined in E. faecalis strains and except chloramphenicol in E. faecium strains harbouring the vancomycin resistance genes. In conclusion, it was thought the buffalo clotted creams offered for consumption in Afyonkarahisar may have potential risk for public health in terms of VRE species. To our knowledge, this is the first study showing the presence of VRE in the clotted cream samples by PCR in Turkey.